Natural Resources Sustainability An introductory synthesis - Lant, Christopher (Open textbook library., 2023)
This text has evolved from 20 semesters teaching the undergraduate courses Geography, People, and the Environment and Environment and Society. It is designed for freshmen through junior-level courses at community, junior and four-year colleges and universities in the United States. Focused upon the dilemma of environmental sustainability, geography and the emergent field of ecological economics are emphasized in a trans-disciplinary framework. It provides—in a one semester or one quarter undergraduate course that requires no prerequisites—a fundamental background in the essentials students need to deal with natural resource and environmental issues as an informed citizen while building a foundation for further study.